Historical Determinism in the Constitution of the United States and the Spanish Constitution of 1812 - Gurpegui, José Antonio (Complutense Journal of English Studies, 2018)
The Constitution of the United States has not been a document specially referred to, nor considered, by Spanish academics who have studied the Constitution of 1812. Even the constitutionalists gathered in Cádiz fled from anything that could evoke a republican and federalist constitution being their purpose radically different. In a general way, it has been the French Constitution of 1791, the reference text “par excellece”. But, beyond the liberal principles that Americans and most of the Spaniards embraced, there were some historical coincidences in the United States and Spain which conditioned in a similar way the final result of both political documents.